Determinants of Village Expansion Policy in Takalar Regency - Mudassir Hasri Gani; Hasnawi Haris; Herman H; Andi Kasmawati; Alfiana Damasinta (Kirana Publisher (KNPub), 2026)
Village expansion policy has become an important instrument of rural administrative reform in Indonesia, aiming to improve governance effectiveness, expand access to public services, and accelerate local development. However, the success of village expansion remains uneven across regions, particularly in rural areas with varying institutional and fiscal capacities. This study examines the determinants of successful village expansion policy implementation in Takalar Regency. Specifically, the research analyzes how institutional capacity, leadership quality, fiscal support, community participation, and governance transparency influence the effectiveness of newly established village administrations. Using a quantitative approach, data were collected through structured surveys involving village officials, community leaders, and residents from selected expanded villages in Takalar Regency. The data were analyzed using Structural Equation Modeling (SEM-PLS) to assess both direct and indirect relationships among variables. The findings indicate that institutional capacity and leadership quality are the most significant predictors of successful village expansion, followed by fiscal support and community participation. Governance transparency also plays a moderating role by strengthening trust and collaboration between local government and citizens. The study contributes to the literature on decentralization and rural governance by providing empirical evidence from the village-level reform context in Indonesia. Practically, the findings suggest that village expansion policies should not focus solely on territorial division, but also on strengthening administrative readiness, leadership competence, fiscal sustainability, and participatory governance. These insights are relevant for policymakers seeking to enhance the long-term effectiveness of rural administrative restructuring in developing countries.